The Growth Comparison of Haematococcus Pluvialis in Two Different Medium - Dina Soes Putri; Siti Alaa (Universitas Islam Negeri Mataram, 2019)
Microalgae is an aquatic microorganism that conducts photosynthesis. It plays a vital role as an oxygen producer in the marine ecosystem. A freshwater microalgae, Haematococcus pluvialis, has been utilized as a health supplement and industrial application which is beneficial for human. In addition to physical and chemical factors, nutrient composition is one crucial thing that contributes to the growth of microalgae. This present study aimed to determine and compare the growth rate of Haematococcus pluvialis cultivated in two culture medium, Walne’s and Guillard. The culture conditions observed were light intensity, photoperiod of light-dark hours, temperature, inoculum concentration of medium’s liquid, and cell density. This study confirmed that Walne’s media produced much higher biomass (247x104 cells/mL) than Guillard’s medium (209.6x104 cells/mL). The aspect to be further performed on H. pluvialis biomass is exploring its high-value bio compound.